Um resgate às frações contínuas - Santos, Antônio Carlos Damasceno dos (2014)
The rescue A continuous fractions got their start with a historical approach, showing what is known today about this issue is the result of studies by various mathematical world. Besides the story, the text is divided into five chapters and an appendix, showing through theorems and examples advantage, indisputable, the approximation of real numbers by rational numbers, using the device of continued fractions.